The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2217/epi-2016-0097
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and epigenetic mechanisms underlying arsenic-associated diabetes mellitus: a perspective of the current evidence

Abstract: Chronic exposure to arsenic has been associated with the development of diabetes mellitus (DM), a disease characterized by hyperglycemia resulting from dysregulation of glucose homeostasis. This review summarizes four major mechanisms by which arsenic induces diabetes, namely inhibition of insulin-dependent glucose uptake, pancreatic β-cell damage, pancreatic β-cell dysfunction and stimulation of liver gluconeogenesis that are supported by both in vivo and in vitro studies. Additionally, the role of polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…For example, a number of studies have shown that arsenic can play a role in glucose dysfunction and insulin resistance (Tseng 2004). Arsenic increases the production of ROS and free radicals, which have been implicated in chronic inflammation and apoptosis of pancreatic β-cells (Martin et al 2017). Arsenic also upregulates the expression of inflammatory genes such as NFkB, tumor necrosis factor- α (TNF- α ), and interleukin (IL)-6 (Tseng 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a number of studies have shown that arsenic can play a role in glucose dysfunction and insulin resistance (Tseng 2004). Arsenic increases the production of ROS and free radicals, which have been implicated in chronic inflammation and apoptosis of pancreatic β-cells (Martin et al 2017). Arsenic also upregulates the expression of inflammatory genes such as NFkB, tumor necrosis factor- α (TNF- α ), and interleukin (IL)-6 (Tseng 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Arsenic also upregulates the expression of inflammatory genes such as NFkB, tumor necrosis factor- α (TNF- α ), and interleukin (IL)-6 (Tseng 2004). These inflammatory factors can injure the pancreas and interfere with glucose-mediated insulin secretion (Martin et al 2017; Walton et al 2004). Several environmental pollutants have been shown to impair thermogenic adipose tissue involved in glucose and lipid metabolism (Zhang et al 2016), and arsenic’s effect on adiposity, specifically on brown and beige adipocytes, may also be a mechanism by which it affects diabetes risk (Maull et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation, histone modification and microRNA expression have been identified as the prominent epigenetic mechanisms of i As toxicity . i As alteration of epigenetic mechanisms has also been linked to an up‐regulation of cancer‐related genes, as well as a down‐regulation of programmed cell death .…”
Section: Mechanisms Involved In Arsenic Tumorigenesismentioning
confidence: 99%
“…Other emerging risk factors for type 2 DM and CVD include the gut microbiome ( 256 258 ), gallbladder disease ( 259 ), environmental exposures ( 260 262 ), and the impact of sugar-sweetened beverages intake on satiety ( 263 ). Research on these emerging factors in Hispanics/Latinos has been limited.…”
Section: Etiology Of Type 2 Dm In Hispanics/latinosmentioning
confidence: 99%